Preparation and Properties of Thermoresponsive P(N-Isopropylacrylamide-co-butylacrylate) Hydrogel Materials for Smart Windows - Jae-Hyung Park; Ji-Won Jang; Jae-Hak Sim; Il-Jin Kim; Dong-Jin Lee; Young-Hee Lee; Sang-Hui Park; Han-Do Kim (International Journal of Polymer Science)
Thermoresponsive polymers that exhibit phase transition in response to temperature change can be used as material for smart windows because they can control solar light transmission depending on the outside temperature. The development of thermoresponsive polymers for a smart window that can be used over a wide temperature range is required. Therefore, to obtain smart window materials that can be used at various temperatures, three-dimensional thermoresponsive P(NIPAm-co-BA) hydrogels were prepared by free radical polymerization from main monomer N-isopropylacrylamide, comonomer butyl acrylate, and crosslinking agent N,N′-methylenebisacrylamide (MBAm) in this study. This study examined the effect of BA content on the lower critical solution temperature (LCST) and the solar light transmittance of crosslinked P(NIPAm-co-BA) hydrogel films. The LCST of hydrogel films was found to be significantly decreased from 34.3 to 29.5°C with increasing BA content from 0 to 20 mol%. It was found that the transparent films at T=25°C (T<LCST) were converted to translucent films at a higher temperature (T=45°C) (T>LCST). These results suggested that the crosslinked P(NIPAm-co-BA) hydrogel materials prepared in this study could have high potential for application in smart window materials.